Exegesis and theology according to the Synod on the Word of God - Uríbarri Bilbao, Gabino (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The XIIth Bishops’ Synod on «The Word of God in the Life and Mission of the Church» (Rome, october, 5-26th, 2009), is focused in this article. Most relevant eclesial and theological subjects, like the presence of the Scripture in the Church, the relationship between exegesis and theology, or the requirements for a truly theological exegesis, where discussed during the Synod. This article takes into account the main documents produced as preparation for the Synod, during its sessions, or at the end.